Answer:
2x - 2
Explanation:
Here is the completer question
lim as Δx → 0 [(x + Δx)²- 2(x + Δx) + 3 - (x² - 2x + 3)]/Δx
Solution
lim as Δx → 0 [(x + Δx)²- 2(x + Δx) + 3 - (x² - 2x + 3)]/Δx
Expanding the brackets, we have
lim as Δx → 0 [(x² + 2xΔx + (Δx)²- 2x - 2Δx + 3 - x² + 2x - 3)]/Δx
Collecting like terms. we have
lim as Δx → 0 [(x² - x² + 2xΔx - 2Δx + (Δx)²- 2x + 2x + 3 - 3)]/Δx
Simplifying, we have
lim as Δx → 0 [(0 + 2xΔx - 2Δx + (Δx)² + 0 + 0)]/Δx
lim as Δx → 0 [2xΔx - 2Δx + (Δx)²]/Δx
Dividing through by Δx, we have
lim as Δx → 0 [2x - 2 + (Δx)]
Inserting Δx = 0, we have
= lim as Δx → 0 (2x -2 + 0)
= 2x -2
So lim as Δx → 0 [(x + Δx)²- 2(x + Δx) + 3 - (x² - 2x + 3)]/Δx = 2x -2